Sandwich structure and method of manufacturing same

The sandwich structure, featuring a core material and fiber reinforcement layers with high thermal conductivity, addresses the challenges of material strength and bonding in existing designs, resulting in enhanced heat dissipation and mechanical performance.

JP7661700B2Active Publication Date: 2025-04-15TORAY INDUSTRIES INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020564285
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-11
Publication Date
2025-04-15
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Existing sandwich structures face issues with insufficient strength of thermally conductive materials, peeling of materials due to inadequate bonding, and a trade-off between thermal conductivity and mechanical rigidity.

Method used

A sandwich structure comprising a core material and fiber reinforcement materials on both sides, where at least one fiber reinforcement material includes a sheet-like thermal conductivity material with an in-plane thermal conductivity of 300 W/m·K or more, ensuring comprehensive coverage of the thermal conductive material's edges and surfaces.

Benefits of technology

The proposed sandwich structure achieves excellent heat dissipation and mechanical properties, even with insufficient strength of the thermal conductive material or inadequate bonding, by effectively distributing stress and preventing peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661700000002
    Figure 0007661700000002
  • Figure 0007661700000003
    Figure 0007661700000003
  • Figure 0007661700000004
    Figure 0007661700000004
Patent Text Reader

Abstract

The purpose of the present invention is to provide a sandwich structure that achieves both excellent heat radiation and excellent mechanical characteristics. To this end, the sandwich structure according to the present invention has the following configuration. That is, the sandwich structure has a core material (I) and fiber-reinforced materials (II) arranged on both surfaces of the core material (I), wherein at least one of the fiber-reinforced materials (II) includes a sheet-shaped heat conduction material (III) having an in-plane heat conduction ratio of 300 W / m・K or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sandwich structure, a housing using the same, and a method for manufacturing the sandwich structure. [Background technology]

[0002] In recent years, market demands for heat dissipation have been increasing year by year for industrial products such as automobiles, aircraft, and electronic devices. To meet such demands, molded products with high thermal conductivity are widely used in various industrial applications. In particular, sandwich structures containing thermally conductive materials with high thermal conductivity have excellent mechanical properties in addition to excellent heat dissipation, and are therefore expected to be used in various products. In particular, sandwich structures containing thermally conductive materials and high-strength materials have been widely studied.

[0003] Patent Document 1 describes an invention of a sandwich structure in which a thermally conductive material and a rigidity retaining material are laminated. It is said that by laminating a thermally conductive material and a rigidity retaining material, it is possible to obtain a sandwich structure that has both excellent thermal conductivity and excellent rigidity.

[0004] Patent Document 2 describes an invention of a sandwich structure in which a graphite sheet having excellent thermal conductivity is laminated with a support sheet on both sides of the graphite sheet, and a sealing spacer of approximately the same thickness as the graphite sheet is attached to at least one end face of the graphite sheet. By attaching the sealing spacer to the periphery of the graphite sheet, it is said that the structure has excellent thermal conductivity and mechanical strength, prevents graphite powder from being detached from the end faces, is easy to handle since there is no knife-like edge, and has the effect of suppressing peeling.

[0005] Patent Document 3 describes an invention for a highly thermally conductive housing in which a laminate of graphite sheets is covered with a resin layer. It is said that by covering the edges of the graphite sheets with resin, it is possible to prevent peeling between the graphite films. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 002457 [Patent Document 2] JP 2007-44994 A [Patent Document 3] JP 2006-95935 A Summary of the Invention [Problem to be solved by the invention]

[0007] The sandwich structure in Patent Document 1 has a problem in that the strength of the heat conductive material is insufficient because all edges of the heat conductive material are exposed. Also, if the bonding strength between the heat conductive material and the rigidity retaining material is insufficient, there is a possibility that the edges of the sandwich structure will peel off.

[0008] In the sandwich structure of Patent Document 2, the ends of the graphite sheets are protected by sealing spacers, but the adjustment of the thickness and position of the sealing spacers is complicated, resulting in low processability. In addition, if the bonding strength between the sealing spacer and the support sheet is insufficient, peeling may occur from the ends of the sandwich structure.

[0009] In the highly thermally conductive case of Patent Document 3, the surface and edges of the graphite sheet are covered with resin to protect the graphite sheet, but due to protection with resin, the rigidity and strength are low.

[0010] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a sandwich structure which combines excellent heat dissipation properties with excellent mechanical properties. [Means for solving the problem]

[0011] In order to solve the above problems, the sandwich structure of the present invention has the following configuration.

[0012] A sandwich structure having a core material (I) and fiber reinforcement materials (II) arranged on both sides of the core material (I), wherein at least one of the fiber reinforcement materials (II) contains a sheet-like thermally conductive material (III) having an in-plane thermal conductivity of 300 W / m K or more. Effect of the Invention

[0013] According to the present invention, a structure that combines excellent heat dissipation properties and excellent mechanical properties can be obtained even when the strength of the thermal conductive material is insufficient or when the bonding between the thermal conductive material and the material that protects the thermal conductive material is insufficient. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a sandwich structure of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing another embodiment of the sandwich structure of the present invention. [Diagram 3] FIG. 13 is a schematic diagram showing a state of heat dissipation evaluation. [Figure 4] FIG. 2 is a schematic cross-sectional view of the sandwich structure produced in Example 1. [Diagram 5] FIG. 2 is a schematic cross-sectional view of the sandwich structure produced in Example 2. [Figure 6] FIG. 2 is a schematic cross-sectional view of the sandwich structure produced in Comparative Example 1. [Figure 7] FIG. 2 is a schematic cross-sectional view of a sandwich structure produced in Comparative Example 2. [Figure 8] FIG. 4 is a schematic cross-sectional view of a sandwich structure produced in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below.

[0016] <Sandwich structure> The sandwich structure of the present invention has a core material (I) and a fiber reinforcement material (II) arranged on both sides of the core material (I). In this specification, the sandwich structure is a structure in which a skin material having a higher elastic modulus than the core material is arranged on both sides of the core material. In the sandwich structure of the present invention, the skin material is a fiber reinforcement material (II), and at least one of the fiber reinforcements (II) includes a sheet-like thermal conductive material (III). In addition, the sheet-like refers to a thin and wide material. Specifically, the thickness is 0.01 μm or more and 10 mm or less, and the aspect ratio of the width to the thickness is 10 or more.

[0017] In the sandwich structure of the present invention, at least one of the fiber reinforcements (II) contains a sheet-like heat conductive material (III) (hereinafter, may be simply referred to as heat conductive material (III)). The term "containing" here means that the heat conductive material (III) is present as a part of the layer of the fiber reinforcement (II) in the laminated structure of the sandwich structure.

[0018] For example, in the case of FIG. 1, in which the fiber reinforcement (II) 3 covers one surface (upper surface in FIG. 1) and one end surface (right end surface in FIG. 1) of the thermal conductive material (III) 4, and in the case of FIG. 2, in which the fiber reinforcement (II) 3 covers both surfaces (both surfaces) and all end surfaces of the thermal conductive material (III) 4, that is, in which the fiber reinforcement (II) contains the thermal conductive material (III), it can be said that the fiber reinforcement (II) contains the thermal conductive material (III). On the other hand, in the case of FIG. 6, in which all end surfaces of the thermal conductive material (III) (graphite sheet 9) are exposed, that is, in which only the thermal conductive material (III) can be considered to form an independent layer, this is excluded from the concept of "including". In this way, by including the thermal conductive material (III) in the fiber reinforcement (II), the fiber reinforcement (II) bears the stress applied to the sandwich structure, and the transfer of the stress to the thermal conductive material (III) is suppressed, and the destruction of the thermal conductive material (III) can be suppressed.

[0019] In the sandwich structure of the present invention, it is preferable that at least one of the fiber reinforcements (II) covers at least two end faces of the thermally conductive material (III), and it is further preferable that at least one of the fiber reinforcements (II) covers both faces and all end faces of the thermally conductive material (III), i.e., it encapsulates the thermally conductive material (III).

[0020] In the present invention, the fiber reinforcement (II) may cover the heat conductive material (III) via another member such as an adhesive, a buffer material, etc. Also, there may be a gap between the fiber reinforcement (II) and the heat conductive material (III).

[0021] However, in the present invention, it is preferable that at least one end face of the heat conductive material (III) is in direct contact with the fiber reinforcement material (II) without any other member. It is also preferable that at least one surface of the heat conductive material (III) is in contact with the fiber reinforcement material (II). By directly contacting the heat conductive material (III) with the fiber reinforcement material (II) in this way, the heat transferred from the surface of the sandwich structure can be quickly transferred from the fiber reinforcement material (II) to the heat conductive material (III).

[0022] In addition, in the thickness direction, the surface of the thermally conductive material (III) is preferably arranged within 0.01 mm to 0.3 mm from the surface of the fiber reinforcement material (II) containing the thermally conductive material (III). More preferably, it is within 0.1 mm to 0.2 mm. By arranging them in this way, the distance between the heat source and the thermally conductive material (III) is shortened, and heat from the heat source can be quickly transferred from the surface of the sandwich structure to the thermally conductive material (III). On the other hand, if the distance between the surface of the thermally conductive material (III) and the surface of the sandwich structure is too short, the mechanical properties may be deteriorated.

[0023] The sandwich structure of the present invention preferably has a bending rigidity per unit width of 0.5 N·m or more, more preferably 1.0 N·m or more, and even more preferably 1.5 N·m or more. The higher the bending rigidity per unit width of the sandwich structure, the more preferable it is, so there is no particular upper limit to the bending rigidity per unit width, but it is usually about 1000 N·m. By setting the bending rigidity per unit width within the above-mentioned range, the sandwich structure becomes a rigid structure and can be suitably used for housings and the like. The bending rigidity per unit width is determined by the elastic modulus E (Pa) and second moment of area I (m 4 ) and the width b (m) of the sandwich structure, it can be calculated using the following formula: · Bending stiffness per unit width (N·m) = E (Pa) × I (m 4 ) / b(m) In addition, when the cross section of the sandwich structure is rectangular, the second moment of area I of the rectangular cross section is bh 3 / 12(m 4 ), it can be calculated using the following formula: · Bending stiffness per unit width (N·m) = E (Pa) × h 3 (m 3 ) / 12 As a means for setting the bending rigidity per unit width within the above range, for example, a method of using a fiber reinforced material (II) as a skin material as in the sandwich structure of the present invention, or a method of increasing the thickness of the sandwich structure, can be mentioned.

[0024] The maximum thickness of the sandwich structure of the present invention is preferably 0.3 mm to 3.0 mm, more preferably 0.5 mm to 1.5 mm. Although reducing the thickness of the sandwich structure has the effect of reducing the weight, a sandwich structure thinner than 0.3 mm may lack rigidity.

[0025] [Thermal Conductive Material (III)] In the present invention, the thermally conductive material (III) is in the form of a sheet. The thermal conductivity of the thermally conductive material (III) is 300 W / m·K or more. The thermal conductivity of the thermally conductive material (III) is preferably 500 W / m·K or more, more preferably 1000 W / m·K or more. The higher the thermal conductivity of the thermally conductive material, the more preferable it is. Therefore, there is no particular limit to the upper limit of the thermal conductivity of the thermally conductive material, but a thermally conductive material having an in-plane thermal conductivity of about 2000 W / m·K is known. If the thermal conductivity of the thermally conductive material (III) is 300 W / m·K or more, the heat diffusion in the in-plane direction of the sandwich structure is excellent, and the heat dissipation of the sandwich structure is excellent. The thermal conductivity of the thermally conductive material (III) can be measured by setting a sample in a sample holder for in-plane measurement by the laser flash method, and setting the size of the sample to a diameter of about 20 to 30 mm and a thickness of 1 mm or less. For materials that do not easily absorb laser light, a thin and uniform blackening film is formed on the front surface of the sample. For materials with low emissivity at the temperature measurement wavelength of the infrared detection element, a similar treatment is performed on the back surface of the sample.

[0026] The material of the thermally conductive material (III) is not particularly limited as long as it has an in-plane thermal conductivity of 300 W / m K or more. For example, ceramics, metals, graphite, and highly thermally conductive resins in which a highly thermally conductive filler has been added to the resin to increase the thermal conductivity can be used.

[0027] In the sandwich structure of the present invention, the thermally conductive material (III) preferably includes a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet, and more preferably is a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet. Examples of the ceramic sheet include sheets of silica, zirconia, alumina, boron nitride, silicon carbide, silicon nitride, etc. Examples of the metal sheet include sheets of titanium, aluminum, magnesium, iron, silver, gold, platinum, copper, nickel, or alloys mainly composed of these elements.

[0028] Metal sheets are relatively inexpensive, and among them, copper sheets are inexpensive and have excellent thermal conductivity, so they are preferable from the viewpoint of raw material costs.Graphite sheets have a small specific gravity and excellent thermal conductivity, so they are particularly preferable in the present invention from the viewpoint of improving the light weight and heat dissipation of the sandwich structure.

[0029] Examples of graphite sheets include sheets made by mixing graphite powder with a binder resin, or sheets made by rolling expanded graphite, sheets made by laminating carbon atoms on a substrate by a CVD method using a hydrocarbon gas and then annealing, sheets made by graphitizing a polymer film, etc. Among these, sheets made by graphitizing a polymer film are preferred because they have very high thermal conductivity.

[0030] In the present invention, the thermally conductive material (III) preferably includes a laminated structure of a plurality of thermally conductive sheets, and more preferably is a laminated structure of a plurality of thermally conductive sheets. In particular, the orientation of the graphene structure in the graphite sheet affects the thermal conductivity, and generally, a thinner graphite sheet has a higher thermal conductivity. Therefore, when a graphite sheet is used as the thermally conductive sheet, the heat dissipation of the sandwich structure can be improved by using a laminated structure of a plurality of sheets as the thermally conductive material (III). In this case, it is preferable that the plurality of thermally conductive sheets constituting the thermally conductive material (III) are in direct contact with each other without the intervention of an adhesive or the like. By directly contacting the thermally conductive sheets with each other, the proportion of the thermally conductive material (III) in the sandwich structure can be increased, and the heat dissipation of the sandwich structure is improved. In addition, by directly contacting the thermally conductive sheets with each other, the heat diffusion in the out-of-plane direction is also excellent. The number of laminated sheets of the thermally conductive sheets is preferably 2 to 10, more preferably 3 to 5. Increasing the number of laminated sheets improves the heat dissipation of the sandwich structure. On the other hand, if the number of layers is increased too much, the processability decreases.

[0031] The average thickness of the thermal conductive material (III) is preferably 0.01 μm or more and 2.0 mm or less, more preferably 5 μm or more and 1.0 mm or less, and even more preferably 15 μm or more and 0.5 mm or less. If the average thickness of the thermal conductive material (III) is too small, the heat dissipation of the sandwich structure decreases, and if the average thickness of the thermal conductive material (III) is too large, the sandwich structure becomes heavy. The method for measuring the average thickness of the thermal conductive material (III) is to measure the thickness of nine points of the thermal conductive material (III) to one decimal place using a micrometer, and the average value is taken as the average thickness. The measurement points are measured at three points in each of the vertical and horizontal directions so that the intervals between each measurement point and the adjacent point or the sample end are equal in the vertical and horizontal directions, for a total of nine points.

[0032] Core In the present invention, it is preferable that the core material (I) contains a porous body, and it is more preferable that the core material (I) is a porous body. The core material (I) contains a porous body, which is advantageous in terms of the light weight of the sandwich structure. In addition, when the thermal conductive material (III) is contained in the fiber reinforcement material (II), the core material (I), which is a porous body, is crushed or expanded in the out-of-plane direction, so that the thermal conductive material (III) is not displaced, and the fiber reinforcement material (II) can contain the thermal conductive material (III).

[0033] When the core material (I) is a porous body, the volume content of voids in the core material (I) is preferably 10% or more and 85% or less, more preferably 20% or more and 85% or less, relative to the apparent volume of the core material (I), and even more preferably 50% or more and 80% or less, from the viewpoint of achieving both light weight and mechanical properties.

[0034] When the core material (I) is a porous body, it is preferable that the porous body is made of a fiber-reinforced resin. Here, the fiber-reinforced resin is a resin reinforced with continuous or discontinuous fibers. The continuous reinforcing fibers mean reinforcing fibers that are continuous in at least one direction over a length of 15 mm or more, preferably 100 mm or more. As the fiber-reinforced resin reinforced with continuous fibers, unidirectional fiber-reinforced resin, woven fiber-reinforced resin, etc. can be used. As the fiber-reinforced resin reinforced with discontinuous fibers, either short fiber-reinforced resin or long fiber-reinforced resin can be used. In addition, as the non-fiber-reinforced resin, a resin sheet or a resin foam can also be used.

[0035] Regardless of whether the core material (I) contains a resin, whether it is a fiber-reinforced resin or a non-fiber-reinforced resin, the resin is not particularly limited and may be a thermosetting resin or a thermoplastic resin. Examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), and liquid crystal polyesters; polyolefins such as polyethylene (PE), polypropylene (PP), and polybutylene; polyarylene sulfides such as polyoxymethylene (POM), polyamide (PA), and polyphenylene sulfide (PPS); and fluorine-based resins such as polyketone (PK), polyether ketone (PEK), polyether ether ketone (PEEK), polyether ketone ketone (PEKK), polyether nitrile (PEN), and polytetrafluoroethylene. Examples of the resin include crystalline resins, amorphous resins such as "styrene-based resins, polycarbonate (PC), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyphenylene ether (PPE), polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polysulfone (PSU), polyethersulfone, and polyarylate (PAR)" and other resins, phenol-based resins, phenoxy resins, and thermoplastic elastomers such as polystyrene-based, polyolefin-based, polyurethane-based, polyester-based, polyamide-based, polybutadiene-based, polyisoprene-based, fluorine-based resins, and acrylonitrile-based, as well as copolymers and modified products thereof. Among these, polyolefins are preferred from the viewpoint of the light weight of the resulting sandwich structure. In particular, when the core material (I) is a porous body, polyolefins are preferred to synergize the lightweight effect. Also, polyamides are preferred from the viewpoint of strength. In particular, when the core material (I) is a porous body made of a fiber-reinforced resin, polyamide is preferred from the viewpoint of the interfacial bonding strength between the reinforcing fibers and the resin.Examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol (resol) resin, urea resin, melamine resin, polyimide resin, maleimide resin, benzoxazine resin, and a blend of two or more of these. Among these, particularly when the core material (I) is a porous body made of a fiber-reinforced resin, an epoxy resin is preferably used from the viewpoint of the interfacial bonding strength between the reinforcing fiber and the resin.

[0036] Furthermore, the resin may contain, depending on its application, fillers such as mica, talc, kaolin, hydrotalcite, sericite, bentonite, xonotlite, sepiolite, smectite, montmorillonite, wollastonite, silica, calcium carbonate, glass beads, glass flakes, glass microballoons, clay, molybdenum disulfide, titanium oxide, zinc oxide, antimony oxide, calcium polyphosphate, graphite, barium sulfate, magnesium sulfate, zinc borate, calcium borate, aluminum borate whisker, potassium titanate whisker, and polymer compounds; conductive materials such as metals, metal oxides, carbon black, and graphite powder; halogen-based flame retardants such as brominated resins, antimony-based flame retardants such as antimony trioxide and antimony pentoxide, phosphorus-based flame retardants such as ammonium polyphosphate, aromatic phosphate, and red phosphorus; and other additives such as metal borates, metal carboxylates, and aromatic sulfonimide metal salts. Organic acid metal salt flame retardants, inorganic flame retardants such as zinc borate, zinc, zinc oxide and zirconium compounds, nitrogen-based flame retardants such as cyanuric acid, isocyanuric acid, melamine, melamine cyanurate, melamine phosphate and nitrogenated guanidine, fluorine-based flame retardants such as PTFE, silicone-based flame retardants such as polyorganosiloxane, metal hydroxide-based flame retardants such as aluminum hydroxide and magnesium hydroxide, and other flame retardants, cadmium oxide, zinc oxide, cuprous oxide Flame retardant assistants such as cupric oxide, ferrous oxide, ferric oxide, cobalt oxide, manganese oxide, molybdenum oxide, tin oxide and titanium oxide, pigments, dyes, lubricants, release agents, compatibilizers, dispersants, crystal nucleating agents such as mica, talc and kaolin, plasticizers such as phosphate esters, heat stabilizers, antioxidants, coloring inhibitors, ultraviolet absorbers, flow modifiers, foaming agents, antibacterial agents, vibration dampers, deodorants, sliding modifiers, and antistatic agents such as polyether ester amides may also be added. In particular, when the application is for electrical and electronic equipment, automobiles, aircraft, etc., flame retardancy may be required, and phosphorus-based flame retardants, nitrogen-based flame retardants and inorganic flame retardants are preferably added. In order to maintain a good balance between the mechanical properties of the resin used and the resin fluidity during molding while exhibiting a flame retardant effect, the amount of the flame retardant is preferably 1 to 20 parts by mass, more preferably 1 to 15 parts by mass, per 100 parts by mass of the resin.

[0037] From the viewpoint of the light weight of the sandwich structure, the specific gravity of the core material (I) is preferably 0.01 to 1.5, more preferably 0.1 to 1.3, and even more preferably 0.3 to 1.1. The specific gravity can be measured by cutting out a piece of the core material (I) and measuring it in accordance with ISO1183 (1987) or ISO0845 (1988).

[0038] When the core material (I) is a porous body and the porous body is made of a fiber-reinforced resin, there is no particular restriction on the type of reinforcing fiber contained therein. For example, carbon fiber, glass fiber, aramid fiber, alumina fiber, silicon carbide fiber, boron fiber, metal fiber, natural fiber, mineral fiber, etc. can be used, and these may be used alone or in combination of two or more. Among them, PAN-based, pitch-based, rayon-based carbon fibers are preferably used from the viewpoint of high specific strength and specific rigidity and weight reduction effect. In addition, glass fiber can be preferably used from the viewpoint of improving the economic efficiency of the obtained sandwich structure, and it is particularly preferable to use carbon fiber and glass fiber in combination from the viewpoint of balance between mechanical properties and economic efficiency. Furthermore, aramid fiber can be preferably used from the viewpoint of improving the impact absorption and formability of the obtained sandwich structure, and it is particularly preferable to use carbon fiber and aramid fiber in combination from the viewpoint of balance between mechanical properties and impact absorption. In addition, reinforcing fiber coated with metal such as nickel, copper, or ytterbium, or pitch-based carbon fiber can be used from the viewpoint of improving the conductivity of the obtained sandwich structure.

[0039] From the viewpoint of improving mechanical properties, it is preferable that the reinforcing fibers are surface-treated with a sizing agent. Examples of the sizing agent include polyfunctional epoxy resins, acrylic acid-based polymers, polyhydric alcohols, and polyethyleneimines. Specifically, polyglycidyl ethers of aliphatic polyhydric alcohols such as glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitol polyglycidyl ether, arabitol polyglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol polyglycidyl ether, polyacrylic acid, copolymers of acrylic acid and methacrylic acid, acrylic acid, and acrylic acid are preferably used. Examples of suitable epoxy resins include copolymers of glyceryl and maleic acid, or mixtures of two or more of these, polyvinyl alcohol, glycerol, diglycerol, polyglycerol, sorbitol, arabitol, trimethylolpropane, pentaerythritol, and polyethyleneimine containing a large number of amino groups per molecule. Among these, glycerol triglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether are preferably used because they contain a large number of highly reactive epoxy groups per molecule, are highly water-soluble, and are easy to apply.

[0040] Particularly preferred as the core material (I) in the present invention is a porous body made of fiber-reinforced resin having a structure in which discontinuous reinforcing fibers form a three-dimensional network and the intersections of the discontinuous fibers are bonded by resin. By bonding the discontinuous fibers by resin, the shear modulus of the core material (I) is increased, and the rigidity of the sandwich structure is increased. This embodiment will be described below.

[0041] In such a fiber-reinforced resin, the discontinuous fibers are preferably present as fine strands of less than 500 fibers, and more preferably present dispersed as single fibers. The fiber length of the discontinuous fibers is preferably 1 to 50 mm, and more preferably 3 to 30 mm. If the fiber length is 1 mm or more, the reinforcing effect of the discontinuous fibers can be efficiently exhibited. Also, if the fiber length is 50 mm or less, the dispersion of the discontinuous fibers can be maintained well.

[0042] The ratio of the number of bonded portions where single filaments of the discontinuous fibers are bonded to each other by a resin to the total number of crossing portions where the discontinuous fibers cross each other is 50% or more, more preferably 70% or more, and even more preferably 90% or more.

[0043] From the viewpoint of achieving both mechanical properties and moldability, the mass proportion of the discontinuous fibers in the core material (I) is preferably 5 to 60 mass %, more preferably 10 to 50 mass %, and even more preferably 15 to 40 mass %.

[0044] In a porous body made of fiber-reinforced resin, it is preferable that 30% or more, more preferably 50% or more, and even more preferably 80% or more of the surface of the discontinuous fibers is covered with resin. By achieving such a coverage, the rigidity of the core material (I) can be increased. The coverage is measured by observing the cross section of the core material (I) with a scanning electron microscope (SEM) to distinguish the reinforcing fibers from the resin.

[0045] [Fiber reinforcement material (II)] In the present invention, the fiber reinforcement material (II) is a member that constitutes a skin material of the sandwich structure, contains reinforcing fibers, and has a higher elastic modulus than the core material (I).

[0046] The material of the fiber reinforced material (II) is not particularly limited as long as it has a larger elastic modulus than the core material (I), and may be a fiber reinforced resin reinforced with continuous fibers or a fiber reinforced resin reinforced with discontinuous fibers. As the fiber reinforced resin reinforced with continuous fibers, a unidirectional fiber reinforced resin or a woven fiber reinforced resin can be used. As the fiber reinforced resin reinforced with discontinuous fibers, either a short fiber reinforced resin or a long fiber reinforced resin can be used. However, from the viewpoint of the mechanical properties of the sandwich structure, it is preferable to use a continuous fiber reinforced resin, and among them, a unidirectional fiber reinforced resin can be more preferably used. On the other hand, from the viewpoint of the shapeability of the sandwich structure, a discontinuous fiber reinforced resin can be preferably used. In addition, the matrix resin of the fiber reinforced resin is not particularly limited, and either a thermosetting resin or a thermoplastic resin can be used, and the same resin as exemplified in the description of the core material (I) above can be used. Furthermore, an additive may be contained in the matrix resin, and examples of the additive include the additives exemplified in the description of the core material (I) above.

[0047] There is no particular limitation on the type of reinforcing fibers contained in the fiber reinforcement material (II), and the same reinforcing fibers as those exemplified in the above description of the core material (I) can be used.

[0048] The content of the reinforcing fibers in the fiber reinforced material (II) is preferably 30 to 90 mass%, more preferably 40 to 80 mass%, and even more preferably 50 to 70 mass% in 100 mass% of the fiber reinforced material (II) from the viewpoint of achieving both mechanical properties and moldability. The range may be any combination of the above upper and lower limits.

[0049] In the sandwich structure of the present invention, the fiber reinforcement material (II) is preferably made of carbon fiber reinforced resin. By using carbon fiber reinforced resin, a sandwich structure having excellent light weight, rigidity, and strength can be easily obtained. Among carbon fibers, pitch-based carbon fibers having high elastic modulus and thermal conductivity are more preferable. By using pitch-based carbon fibers, the rigidity and heat dissipation of the sandwich structure can be improved.

[0050] In the present invention, the fiber reinforcement material (II) may have a laminated structure in which a plurality of sheets of the above-mentioned members are laminated. In the sandwich structure of the present invention, the fiber reinforcement material (II) is preferably made of a unidirectional fiber reinforced resin, and is laminated so that the fiber directions of the fiber reinforcement material (II) between the surface of the fiber reinforcement material (II) containing the thermal conductive material (III) and the thermal conductive material (III) are in multiple directions. By laminating the fiber directions of the fiber reinforced sheet between the surface of the sandwich structure and the thermal conductive material (III) in multiple directions, it is possible to exhibit excellent mechanical properties against stress from any direction.

[0051] <Method of manufacturing sandwich structure> The sandwich structure of the present invention can be preferably produced by the following methods [1] to [3].

[0052] Method [1]: A method for producing a sandwich structure of the present invention, comprising the steps of arranging a precursor of a fiber reinforcement material (II) on at least one surface and at least one end surface of the thermally conductive material (III), hot pressing, and bonding the fiber reinforcement material (II) to both surfaces of the core material (I), in this order.

[0053] Method [2]: A method for producing a sandwich structure of the present invention, comprising the steps of arranging a thermally conductive material (III) having a precursor of fiber reinforcement (II) disposed on at least one surface and at least one end surface thereof in the order of a precursor of a core material (I) / a precursor of a fiber reinforcement (II), and then performing a heat pressing step.

[0054] Method [3]: A method for producing a sandwich structure of the present invention, comprising the steps of arranging a precursor of a fiber reinforcement material (II) on at least one surface and at least one end surface of the thermally conductive material (III), heat pressing, arranging the fiber reinforcement material (II) on both surfaces of a precursor of a core material (I), and heat pressing, in this order.

[0055] In the methods [1] to [3], "arranging a precursor of a fiber reinforcement material (II) on at least one surface and at least one end face of a thermally conductive material (III)" and "a thermally conductive material (III) having a precursor of a fiber reinforcement material (II) arranged on at least one surface and at least one end face" mean that the precursor of the fiber reinforcement material (II) is arranged so as to cover at least one surface and at least one end face of the thermally conductive material (III).

[0056] In the methods [1] to [3], it is preferable that the precursor of the fiber reinforcement material (II) is disposed on both sides of the heat conductive material (III). That is, in the method [2], it is preferable that the "step of arranging in the order of the heat conductive material (III) having the precursor of the fiber reinforcement material (II) disposed on at least one surface and at least one end surface / the precursor of the core material (I) / the precursor of the fiber reinforcement material (II)" is the "step of arranging in the order of the precursor of the fiber reinforcement material (II) / the heat conductive material (III) / the precursor of the fiber reinforcement material (II) / the precursor of the core material (I) / the precursor of the fiber reinforcement material (II)". In addition, in the methods [1] to [3], it is more preferable that the precursor of the fiber reinforcement material (II) is disposed on at least two end surfaces of the heat conductive material (III), and it is further preferable that it is disposed on both sides of the heat conductive material (III), and it is particularly preferable that it is disposed on both sides and all end surfaces of the heat conductive material (III), that is, it contains the heat conductive material (III).

[0057] The precursor of the core material (I) is, for example, a prepreg containing reinforcing fibers and a resin when the core material (I) is a fiber-reinforced resin, or a resin sheet containing a foaming agent or a laminate of resin sheets when the core material (I) is a non-fiber-reinforced resin.

[0058] In the case where the core material (I) is formed of a porous body made of fiber-reinforced resin, which is a preferred embodiment of the present invention, the precursor of the core material (I) can be produced by compressing and impregnating a discontinuous reinforcing fiber mat with a thermoplastic resin film or nonwoven fabric. The discontinuous reinforcing fiber mat is produced, for example, by dispersing discontinuous reinforcing fibers in advance in a strand shape, preferably in a substantially monofilament shape, more preferably in a monofilament shape. More specifically, known techniques include an airlaid method in which discontinuous reinforcing fibers are dispersed in an air flow to form a sheet, a carding method in which discontinuous reinforcing fibers are mechanically scraped into a sheet, and a wet process by the Radlite method in which discontinuous reinforcing fibers are stirred in water and paper is made.

[0059] Examples of means for making the discontinuous reinforcing fibers closer to single fibers in the dry process include a means for providing a fiber opening bar, a means for vibrating the fiber opening bar, a means for making the card finer, and a means for adjusting the rotation speed of the card. Examples of means for making the discontinuous reinforcing fibers closer to single fibers in the dry process include a means for adjusting the stirring conditions of the discontinuous reinforcing fibers, a means for diluting the reinforcing fiber concentration of the dispersion, a means for adjusting the viscosity of the dispersion, and a means for suppressing vortexes when transferring the dispersion. In particular, the discontinuous reinforcing fiber mat is preferably produced by a wet method, and the proportion of reinforcing fibers in the discontinuous reinforcing fiber mat can be easily adjusted by increasing the concentration of the input fibers or adjusting the flow rate (flow rate) of the dispersion and the speed of the mesh conveyor. For example, by slowing down the speed of the mesh conveyor relative to the flow rate of the dispersion, the orientation of the fibers in the obtained discontinuous reinforcing fiber mat is less likely to face the take-up direction, and a bulky discontinuous reinforcing fiber mat can be produced. The discontinuous reinforcing fiber mat may be composed of discontinuous reinforcing fibers alone, or the discontinuous reinforcing fibers may be mixed with a powder-shaped or fibrous matrix resin component, the discontinuous reinforcing fibers may be mixed with an organic or inorganic compound, or the discontinuous reinforcing fibers may be sealed together with a resin component.

[0060] The pressure when the thermoplastic resin film or nonwoven fabric is impregnated into the discontinuous reinforcing fiber mat prepared as described above is preferably 0.5 MPa or more and 30 MPa or less, more preferably 1 MPa or more and 5 MPa or less. If the pressure is less than 0.5 MPa, the thermoplastic resin may not impregnate the discontinuous reinforcing fiber mat, and if it is greater than 30 MPa, it becomes difficult to adjust the thickness of the core material precursor. The temperature when the thermoplastic resin film or nonwoven fabric is impregnated is preferably a temperature equal to or higher than the melting point or glass transition point of the thermoplastic resin, more preferably a temperature equal to or higher than the melting point or glass transition point plus 10 ° C., and even more preferably a temperature equal to or higher than the melting point or glass transition point plus 20 ° C. If the temperature when the thermoplastic resin film or nonwoven fabric is impregnated is too high, decomposition or deterioration of the thermoplastic resin may occur, so it is preferably equal to or lower than the melting point or glass transition point of the thermoplastic resin plus 150 ° C.

[0061] As equipment for realizing the method of impregnating a discontinuous reinforcing fiber mat with a thermoplastic resin film or nonwoven fabric under the above conditions, a compression molding machine or a double belt press machine can be suitably used. The compression molding machine is a batch type, and productivity can be improved by forming an intermittent press system in which two or more machines for heating and cooling are arranged in parallel. The double belt press machine is a continuous type, and is excellent in continuous productivity because continuous processing can be easily performed.

[0062] The precursor of the fiber reinforcement (II) is usually a prepreg containing reinforcing fibers and a resin. For example, a unidirectional fiber prepreg or a woven fiber prepreg reinforced with continuous fibers, or a laminate in which a reinforcing fiber sheet and a resin sheet are laminated, can be mentioned.

[0063] All of the methods [1] to [3] have a step of heat pressing. In this step, a precursor of the fiber reinforcement material (II) is placed on at least one surface and at least one end surface of the thermally conductive material (III), and the thermally conductive material can be contained in the fiber reinforcement material by heat pressing at a temperature required for hardening or melting the resin of the precursor of the fiber reinforcement material (II). The method [3] has two heat pressing steps. In the second heat pressing step, the fiber reinforcement material (II) containing the thermally conductive material and the core material are laminated and heat pressed. The second heat pressing allows the bonding of the fiber reinforcement material and the core material and the molding of the sandwich structure to be performed simultaneously. A compression molding machine can be suitably used as the equipment for the heat pressing. The compression molding machine is of the batch type, and productivity can be improved by forming an intermittent press system in which two or more machines for heating and cooling are arranged in parallel.

[0064] Method [1] is a method in which the fiber reinforcement (II) is impregnated with a thermally conductive material (III) during the molding process of the fiber reinforcement (II), and then the molded fiber reinforcement (II) is bonded to both sides of the core material (I). The means for bonding the core material (I) and the fiber reinforcement (II) is not particularly limited, but for example, the core material (I) and the fiber reinforcement (II) are bonded by hot plate welding, vibration welding, ultrasonic welding, laser welding, resistance welding, induction heating welding, or adhesives. This method is preferably used when the molding conditions such as the molding temperature and molding pressure of the core material (I) and the fiber reinforcement (II) are significantly different.

[0065] Method [2] is a method in which the core material (I) and the fiber reinforcement material (II) are molded and bonded simultaneously. This method can be preferably used when the molding conditions, such as the molding temperature and molding pressure, of the core material (I) and the fiber reinforcement material (II) are similar. This method is preferable from the viewpoint of productivity, since the core material (I) and the fiber reinforcement material (II) can be molded and bonded simultaneously.

[0066] Method [3] is a method in which, during the molding process of the fiber reinforcement (II), the thermally conductive material (III) is impregnated into the fiber reinforcement (II), and then the molded fiber reinforcement (II) is placed on both sides of the precursor of the core material (I) and hot pressed. This is preferable from the viewpoint of productivity, since the bonding of the core material (I) and the fiber reinforcement (II) and the molding of the core material (I) can be performed simultaneously.

[0067] <Case> The housing of the present invention is made using the sandwich structure of the present invention. By using the sandwich structure of the present invention, a housing having both excellent mechanical properties and light weight can be obtained. In addition, from the viewpoint of mass production, it is preferable because it can be molded by high cycle molding such as press molding.

[0068] The housing of the present invention can be obtained, for example, by producing a sandwich structure having a desired housing shape using the above-mentioned method for producing a sandwich structure. EXAMPLES

[0069] The present invention will now be described in more detail with reference to examples.

[0070] (1) Measurement of bending strength and bending modulus of sandwich structure The bending properties of the sandwich structure specimens were measured according to ISO178 (1993). The bending direction was the fiber direction of the outermost surface of the specimen and the direction perpendicular to it, and the number of measurements was n=5. The average values ​​were used as the bending strength and bending modulus. The measurement device used was an Instron Japan Co., Ltd. "Instron" (registered trademark) 5565 type universal material testing machine.

[0071] (2) Heat dissipation evaluation of sandwich structures As shown in Figure 3, a 10 mm x 10 mm rubber spacer 6 with a thickness of 3 mm was attached to the four corners of the back surface of the prepared sandwich structure 1, and the structure was placed on a laboratory bench. A 50 mm x 25 mm micro ceramic heater 5 (Micro Ceramic Heater MS-2 (product name) manufactured by Sakaguchi Electric Heater Co., Ltd.) was placed on one corner of the front surface of the sandwich structure, and the heater was heated at 10 W under constant current and constant voltage. The heat dissipation performance was evaluated based on the heater temperature when it became constant 15 minutes after the start of heating, according to the following criteria. A: Heater temperature below 120℃ (high heat dissipation) B: Heater temperature 120℃ or higher (low heat dissipation).

[0072] (Reference Example 1) Preparation of carbon fiber bundles A polymer mainly composed of polyacrylonitrile was spun and baked to obtain a continuous carbon fiber bundle having a total of 12,000 filaments. A sizing agent was applied to the continuous carbon fiber bundle by a dipping method, and the bundle was dried in heated air at a temperature of 120°C to obtain a carbon fiber bundle. The properties of this carbon fiber bundle were as follows.

[0073] Single fiber diameter: 7μm Mass per unit length: 0.8g / m Density: 1.8g / cm 3 Tensile strength: 4.2GPa Tensile modulus: 230GPa Sizing type: Polyoxyethylene oleyl ether Sizing adhesion amount: 1.5% by mass (Reference Example 2) Preparation of carbon fiber mat The carbon fiber bundle of Reference Example 1 was cut to a fiber length of 6 mm with a cartridge cutter to obtain a chopped carbon fiber bundle. An aqueous dispersion of 0.1 mass % of a surfactant (Polyoxyethylene lauryl ether (product name) manufactured by Nacalai Tesques, Inc.) was prepared, and the dispersion and the chopped carbon fiber bundle were put into a papermaking machine to produce a carbon fiber mat.

[0074] The papermaking machine is equipped with a dispersion tank, a papermaking tank, and a transport section connecting the dispersion tank and the papermaking tank. The dispersion tank is equipped with an agitator and can disperse the dispersion liquid and chopped carbon fiber bundles that have been put in. The papermaking tank is equipped with a mesh conveyor having a papermaking surface at the bottom, and a conveyor capable of transporting the paper-made carbon fiber mat is connected to the mesh conveyor. The papermaking was performed with a fiber concentration in the dispersion liquid of 0.05% by mass. The paper-made carbon fiber mat was dried in a drying oven at 200°C. Then, a 3% by mass aqueous dispersion of a binder (manufactured by Nippon Shokubai Co., Ltd., "Polyment" (registered trademark) SK-1000) was sprayed as a binder on the upper surface of the carbon mat transported by the conveyor. The excess binder was sucked and dried in a drying oven at 200°C to obtain a carbon fiber mat. The basis weight of the obtained carbon fiber mat was 50 g / m 2 It was.

[0075] (Reference Example 3) Preparation of polypropylene resin film 90% by mass of unmodified polypropylene resin (Prime Polymer Co., Ltd., "Prime Polypro" (registered trademark) J105G) was blended with 10% by mass of acid-modified polypropylene resin (Mitsui Chemicals, Inc., "Admer" (registered trademark) QE510). This blend was melt-kneaded in an extruder and then extruded from a T-shaped die. Thereafter, the resin was taken up on a chill roll at 60°C and cooled and solidified to obtain a polypropylene resin film.

[0076] (Reference Example 4) Preparation of epoxy resin film An epoxy resin (base resin: dicyandiamide / dichlorophenylmethylurea curing type epoxy resin) was applied onto release paper using a coater to obtain an epoxy resin film.

[0077] (Reference Example 5) Preparation of unidirectional prepreg The carbon fiber bundles of Reference Example 1 were arranged in one direction in a sheet shape, and two sheets of the epoxy resin film of Reference Example 4 were placed on both sides of the carbon fiber bundles, and the bundles were impregnated with resin by heating and pressurizing to obtain a carbon fiber basis weight of 110 g / m. 2 A unidirectional prepreg having a thickness of 0.1 mm and a mass fraction of the matrix resin of 30 mass % was obtained.

[0078] Example 1 A sandwich structure was produced using the carbon fiber mat of Reference Example 2, the polypropylene resin film of Reference Example 3, the unidirectional prepreg of Reference Example 5, and a graphite sheet (manufactured by Panasonic Corporation, "PGS" (registered trademark) EYGS182307, in-plane thermal conductivity 1000 W / m·K). The carbon fiber mat, the polypropylene resin film, and the unidirectional prepreg were adjusted to a size of 50 mm × 150 mm, and the graphite sheet was adjusted to a size of 40 mm × 140 mm, and then the layers were laminated in the following order: [unidirectional prepreg 0° / graphite sheet / unidirectional prepreg 90° / polypropylene resin film / carbon fiber mat / carbon fiber mat / polypropylene resin film / unidirectional prepreg 90° / unidirectional prepreg 0°], with the fiber direction of the unidirectional prepreg on the surface being the longitudinal direction of the sample. At this time, the graphite sheet was placed in the center of the laminate. This laminate was sandwiched between release films and further sandwiched between tool plates. They were put into a press molding machine with a plate surface temperature of 180°C, and heated and pressed at 3 MPa for 10 minutes to harden the prepreg and impregnate the carbon fiber mat with polypropylene resin. Next, a spacer with a thickness of 1 mm was inserted between the tool plates, and the plate surface temperature was put into a press molding machine with a plate surface temperature of 40°C, and the laminate was cooled down at a surface pressure of 3 MPa to obtain a sandwich structure in which a fiber reinforcement material was arranged around the thermal conductive material. The thickness of the sample was measured with a micrometer and found to be 1.0 mm. By inserting a spacer with a thickness of 1.0 mm between the tool plates, the carbon fiber mat impregnated with the polypropylene resin springs back, and the core material becomes a porous body. In addition, since the sample in this embodiment is a flat plate, the thickness is constant. Therefore, the thickness measured at any point of the sample is the maximum thickness. The same applies to other examples and comparative examples.

[0079] In addition, the bending test specimen was preformed and press molded in the same manner as above, except that the carbon fiber mat, the polypropylene resin film, and the unidirectional prepreg were adjusted to a size of 50 mm x 40 mm, and the graphite sheet was adjusted to a size of 40 mm x 30 mm, to obtain a bending test specimen of a sandwich structure in which a fiber reinforcement material was arranged around the thermal conductive material. A cross-sectional view of the obtained sandwich structure is shown in FIG. 4. In the obtained sandwich structure, as shown in FIG. 4, both sides of the core material 2 have a fiber reinforcement layer consisting of a unidirectional fiber reinforcement material 0°7 and a unidirectional fiber reinforcement material 90°8. In addition, the graphite sheet 9 has a structure in which both sides and all end faces are covered with the fiber reinforcement material, and is protected by the fiber reinforcement material. Therefore, the mechanical properties of the obtained sandwich structure were excellent, and there was no peeling of the graphite sheet or scattering of graphite sheet fragments. In addition, since the graphite sheet is included, the heat dissipation property was also excellent.

[0080] Example 2 The number of unidirectional prepregs was changed, and the layers were laminated in the order of [unidirectional prepreg 0° / unidirectional prepreg 90° / graphite sheet / unidirectional prepreg 90° / unidirectional prepreg 0° / polypropylene resin film / carbon fiber mat / carbon fiber mat / polypropylene resin film / unidirectional prepreg 0° / unidirectional prepreg 90° / unidirectional prepreg 90° / unidirectional prepreg 0° / ]. Except for this, preforming and press molding were performed in the same manner as in Example 1, and a sandwich structure in which a fiber reinforcement material was arranged around the thermal conductive material and a bending test piece of the sandwich structure were obtained. A cross-sectional view of the obtained sandwich structure is shown in FIG. 5. Since the end of the graphite sheet was protected by the fiber reinforcement material, the mechanical properties of the obtained sandwich structure were excellent. In addition, since unidirectional prepregs in multiple directions were laminated on the surface of the graphite sheet, the mechanical properties in the direction perpendicular to the surface fibers were also excellent.

[0081] Comparative Example 1 Preforming and press molding were performed in the same manner as in Example 1, except that the size of the graphite sheet was adjusted to a size of 50 x 150 mm, to obtain a sandwich structure in which all ends of the thermal conductive material were exposed. In addition, when preparing a bending test piece, preforming and press molding were performed in the same manner as in Example 1, except that the size of the graphite sheet was adjusted to a size of 50 mm x 40 mm, to obtain a bending test piece of a sandwich structure in which all ends of the thermal conductive material were exposed. A cross-sectional view of the obtained sandwich structure is shown in FIG. 6. In the obtained sandwich structure, since all ends of the graphite sheet were exposed, peeling occurred between the layers of the graphite sheet.

[0082] Comparative Example 2 Preforming and press molding were performed in the same manner as in Example 2, except that the size of the graphite sheet was adjusted to a size of 50 x 150 mm, to obtain a sandwich structure in which all ends of the thermal conductive material were exposed. In addition, when preparing a bending test piece, preforming and press molding were performed in the same manner as in Example 2, except that the size of the graphite sheet was adjusted to a size of 50 mm x 40 mm, to obtain a bending test piece of a sandwich structure in which all ends of the thermal conductive material were exposed. A cross-sectional view of the obtained sandwich structure is shown in FIG. 7. In the obtained sandwich structure, since all ends of the graphite sheet were exposed, peeling occurred between the layers of the graphite sheet.

[0083] Comparative Example 3 Preforming and press molding were performed in the same manner as in Example 1, except that no graphite sheets were laminated, to obtain a sandwich structure not containing a thermally conductive material. Similarly, when preparing a bending test piece, preforming and press molding were performed in the same manner as in Example 1, except that no graphite sheets were laminated, to obtain a bending test piece of a sandwich structure not containing a thermally conductive material. A cross-sectional view of the obtained sandwich structure is shown in FIG. 8. The obtained sandwich structure had low heat dissipation because it did not contain a thermally conductive material.

[0084] [Table 1] [Industrial Applicability]

[0085] The sandwich structure of the present invention can achieve both excellent heat dissipation and excellent mechanical properties. Therefore, it can be applied to a wide range of industrial fields as structural members for electric and electronic devices, robots, motorcycles, automobiles, and aircraft. In particular, it can be preferably applied to housings for electronic devices and the like that require high heat dissipation. [Explanation of symbols]

[0086] 1. Sandwich structure 2. Core material (I) 3. Fiber Reinforcement Materials (II) 4. Thermal Conductive Materials (III) 5. Heater 6. Rubber spacers 7. Unidirectional fiber reinforced resin 0° 8. Unidirectional fiber reinforced resin 90° 9. Graphite Sheet

Claims

1. A sandwich structure having a core material (I) and fiber reinforcement materials (II) arranged on both sides of the core material (I), wherein at least one of the fiber reinforcement materials (II) contains a sheet-like thermal conductive material (III) having an in-plane thermal conductivity of 300 W / m·K or more, and covers both sides and all end faces of the thermal conductive material (III).

2. 2. The sandwich structure according to claim 1, wherein the thermally conductive material (III) comprises a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet.

3. The sandwich structure according to claim 2, wherein the thermally conductive material (III) comprises a laminated structure of a plurality of the thermally conductive sheets.

4. The sandwich structure according to any one of claims 1 to 3, wherein the surface of the thermally conductive material (III) is located within 0.01 mm or more and 0.3 mm or less from the surface of the fiber reinforcement material (II) containing the thermally conductive material (III).

5. The sandwich structure according to any one of claims 1 to 4, wherein the core material (I) comprises a porous body.

6. The sandwich structure according to claim 5 , wherein the porous body is made of a fiber-reinforced resin.

7. The sandwich structure according to any one of claims 1 to 6, wherein the fiber reinforcement (II) is made of carbon fiber reinforced resin.

8. The fiber reinforcement material (II) is made of a unidirectional fiber reinforced resin, and the fiber reinforcement material between the surface of the fiber reinforcement material (II) containing the heat conductive material (III) and the heat conductive material (III) is laminated so that the fiber directions are in multiple directions. The sandwich structure according to any one of claims 1 to 7.

9. The sandwich structure according to any one of claims 1 to 8, wherein the bending rigidity per unit width is 0.5 N·m or more.

10. The sandwich structure according to any one of claims 1 to 9, wherein the maximum thickness is 0.3 mm or more and 3.0 mm or less.

11. A housing comprising the sandwich structure according to any one of claims 1 to 10.

12. A method for producing a sandwich structure according to any one of claims 1 to 10, comprising the steps of arranging a precursor of a fiber reinforcement material (II) on both sides and all end faces of the heat conductive material (III), a heat pressing step, and a step of joining the fiber reinforcement material (II) to both sides of the core material (I), in this order. The method for producing a sandwich structure.

13. A method for producing a sandwich structure according to any one of claims 1 to 10, comprising the steps of arranging a thermally conductive material (III) having a precursor of fiber reinforcement (II) on both sides and all end faces in the order of a precursor of a core material (I) / a precursor of a fiber reinforcement (II), and a step of hot pressing, in that order.

14. A method for producing a sandwich structure according to any one of claims 1 to 10, comprising the steps of arranging a precursor of a fiber reinforcement material (II) on both sides and all end faces of the heat conductive material (III), a heat pressing step, arranging the fiber reinforcement material (II) on both sides of a precursor of a core material (I), and a heat pressing step, in this order. The method for producing a sandwich structure.

Citation Information

Patent Citations

  • Composite arrangement and methods for manufacturing the composite arrangement

    DE102014006751A1

  • Thermally conductive sheet

    JP2002038033A

  • High thermal conductive frame and graphite prepreg

    JP2006095935A

  • Graphite composite structure, heat radiation member using the structure, and electronic component using the structure

    JP2007044994A

  • Composite structure

    JP2008230237A